Notification-Oriented Programming Language and Compiler - Ronszcka, Adriano Francisco; Ferreira, Cleverson Avelino; Stadzisz, Paulo Cézar; Fabro, João Alberto; Simão, Jean Marcelo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2017: Anais do VII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2017)
The so-called Notification-Oriented Paradigm (NOP) is a new technique to develop software. NOP is a rule-oriented approach where each rule and fact-base element is split in small entities. These entities particularly collaborate by means of precise notifications only when their state changes. This allows carrying out an inference process free of structural and temporal redundancies. Due to its peculiar properties, NOP tends to be an alternative to achieve suitable performance in program execution, easiness in codification level, and appropriate code modularity, structuration and decoupling. In order to validate these supposed features, a framework was implemented in C++. Even though it quite demonstrated the features of the paradigm in terms of execution performance and development process, it still presented a gap therein. In this context, this paper presents a preliminary programming language and compiler to explore NOP features. This new approach simplifies the development in NOP and speedup execution performance.